Glucagon-Like Peptide 1 and Its Cleavage Products Are Renoprotective in Murine Diabetic Nephropathy - Moellmann, Julia; Klinkhammer, Barbara Mara; Onstein, Julia; Stöhr, Robert; Jankowski, Vera; Jankowski, Joachim; Lebherz, Corinna; Tacke, Frank; Marx, Nikolaus; Boor, Peter; Lehrke, Michael (Diabetes (New York, N.Y.), 2018)
Incretin-based therapies, including glucagon-like peptide 1 (GLP-1) receptor agonists and dipeptidyl peptidase 4 (DPP-4) inhibitors, are potent glucose-lowering drugs. Still, only GLP-1 receptor agonists with close peptide homology to GLP-1 (liraglutide and semaglutide) but neither exenatide-based GLP-1 receptor agonists nor DPP-4 inhibitors were found to reduce cardiovascular events. This different response might relate to GLP-1 receptor-independent actions of GLP-1 caused by cleavage products only liberated by GLP-1 receptor agonists with close peptide structure to GLP-1. To test this hypothesis, we directly compared metabolic, renal, and cardiac effects of GLP-1 and its cleavage products in diabetic db/db mice. Using an adeno-associated viral vector system, we overexpressed DPP-4-resistant GLP-1 (7-37 Mut8) and the two GLP-1 cleavage products, GLP-1 (9-37) and GLP-1 (28-37), in diabetic db/db mice. Only GLP-1 (7-37 Mut8), but none of the cleavage products, significantly improved glucose metabolism. Still, all GLP-1 constructs significantly reduced tubulointerstitial renal damage, lowered expression of the tubular injury markers, and attenuated renal accumulation of macrophages and T cells. This was associated with a systemic immunomodulatory effect, which was similarly found in an acute renal ischemia/reperfusion injury model. In conclusion, GLP-1 cleavage products proved sufficient to mediate organ-protective effects, which might help to explain differences between GLP-1 receptor agonists.